Acoustic signal based feature extraction for vehicular classification - Padmavathi, G; Shanmugapriya, D; Kalaivani, M (2010 3rd International Conference on Advanced Computer Theory and Engineering(ICACTE), 2010)
Acoustic signal classification consists of extracting the features from a sound, and of using these features to identify classes the sound is liable to fit.. Different types of noise coming from different vehicles mix in the environment and identifying a particular vehicle is a challenging one. Feature Extraction is done to identify the characteristic of the vehicle. The characteristic of each vehicle will be used to detect its presence and classify its type. Six different features of the vehicle acoustic signals are calculated and then further utilized as input to the classification system. These features include Signal Energy, Energy Entropy, Zero-Crossing Rate, Spectral Roll-Off, Spectral Centroid and Spectral Flux. All these features are extracted from each and every acoustic signal of the vehicles.